The Impact of Food Safety Management System According to ISO 22000:2018 on Competitive Advantage at Arwa Mineral Water Company in Sana’a, Yemen - Shujaa Aldeen, Mohmmed Ahmed; Alarbi, Mustafa Ameen Ahmed (University of Science and Technology Journal for Management and Human Sciences, 2024)
The study aimed to identify the impact of food safety management system (FSMS) according to ISO 22000:2018 by its dimensions (prerequisite programs, hazard analysis and critical control points, training, and continual improvement) on competitive advantage by its dimensions (cost, quality, and customer satisfy). To achieve the study objectives and to test its hypotheses, the descriptive analytical approach was used, and a questionnaire was developed for collecting data from the study population (800) at Arwa Mineral Water Company in Sana’a. The study sample of (259) individuals was selected following a simple random sampling method. The data was processed statistically using SPSS. The study revealed a significant positive impact of all FSMS dimensions based on the ISO 22000:2018 standard on competitive advantage at the surveyed company, where the continual improvement has the most impact, and the training has the least impact on competitive advantage. The study recommends that the surveyed company should pay more attention to continual improvement and training programs in FSMS aiming to reach the efficiency and effectiveness required for FSMS to achieve a highly competitive advantage.